SENSITIVITY AND SPECIFICITY OF THE INDIRECT METHOD FOR DETERMINING THE ESTIMATED FETAL WEIGHT IN THE PREDICTION OF DIABETIC FETOPATHY IN GESTATIONAL DIABETES MELLITUS - Керимова, Сабина Фирдовси кызы; Угдыжекова, Юлия Романовна; Шибельгут, Нонна Марковна; Елгина, Светлана Ивановна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Мозес, Кира Борисовна; Помыткина, Татьяна Евгеньевна (Mother and Baby in Kuzbass, 2022)
A retrospective analysis of data from 85 case histories of women with gestational diabetes mellitus delivered in the perinatal center. The sensitivity of the indirect method for determining the estimated fetal weight in predicting macrosomia in patients with GDM was 0.86, the specificity was 0.65.
Keywords: gestational diabetes; macrosomia